PEMBUATAN MINYAK KELAPA MURNI DENGAN METODE PENGENDAPAN DI DESA RIBANG KECAMATAN KOTING KABUPATEN SIKKA - Rongan, Yoseph; Noni, Sarlina; Yakob Da Rato, Yoseph (Jurnal Biogenerasi, 2024)
Virgin Coconut Oil (VCO) is a coconut-based liquid product characterized by its clear color, distinct coconut aroma, and long shelf life. The purpose of this study is to provide a deeper understanding of the production of Virgin Coconut Oil (VCO) using the sedimentation method and to explore the economic and social potential that VCO production offers to the community. Based on the results of VCO production activities in Ribang Village, Koting Subdistrict, it can be concluded that Virgin Coconut Oil (VCO) is a coconut derivative product with numerous benefits and high economic value. Its simple production process, which uses natural ingredients without chemicals, ensures the preservation of nutrients such as lauric acid, vitamin E, and fatty acids. The advantages of VCO over regular coconut oil include a longer shelf life, superior oil quality, and significant health benefits, such as antimicrobial and antiviral properties. In addition to health benefits, VCO also contributes to beauty care, such as moisturizing skin and hair and addressing various skin issues. Economically, VCO creates opportunities for community empowerment through SMEs, supports eco-friendly production, and has the potential to become a leading export product in the global market.